PENGARUH PEMIKIRAN ZENO TERHADAP EMOSIONAL GENERASI Z : TINJAUAN FILOSOFIS DAN KEAGAMAAN - Husaini, Alpahmi (Studia Sosia Religia, 2025)
The thoughts of Zeno of Citium as the pioneer of Stoic philosophy have a significant influence on the way individuals perceive emotions. This study aims to analyze the influence of Zeno's teachings on the emotional regulation of Generation Z in a contemporary context. Using a qualitative approach and a literature study method, this article presents an interpretation of Zeno's teachings concerning self-control, rationality, and inner peace, as well as their relevance to the emotional challenges faced by Generation Z in the digital era. The research findings indicate that Stoic values can provide a strong foundation for the development of emotional resilience, impulse control, and self-understanding in Generation Z